1996
DOI: 10.1007/bf00114086
|View full text |Cite
|
Sign up to set email alerts
|

Risk taking and failure in de novo savings and loans in the 1980s

Abstract: This article examines failure rates in de novo S&Ls that initiated operations during the 1980-1986 period. Overall failure rates are similar to those for existing institutions but are found to vary significantly by location, time of charter, and organizational form. Both univariate tests and results from a probability-of-failure model indicate that inadequate capital, economic stress, poor management of higher risk lending allowed by broader powers, and operating inefficiencies contributed significantly to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The probability of bank failure, the determinants of that probability, the expected survival time conditional on bank failure, and the determinants of that survival time are estimated for the de novo banks and the established banks using a ''split-population'' duration framework. Schmidt and Witte (1989) developed the split-population approach, and both Cole and Gunther (1996) and Hunter et al (1996) have estimated split-population models of financial institution failure. The central failure concept in these models is the hazard rate, the probability that a bank will fail at time t given that it has survived through all of the previous time periods leading up to time t.…”
Section: Estimation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The probability of bank failure, the determinants of that probability, the expected survival time conditional on bank failure, and the determinants of that survival time are estimated for the de novo banks and the established banks using a ''split-population'' duration framework. Schmidt and Witte (1989) developed the split-population approach, and both Cole and Gunther (1996) and Hunter et al (1996) have estimated split-population models of financial institution failure. The central failure concept in these models is the hazard rate, the probability that a bank will fail at time t given that it has survived through all of the previous time periods leading up to time t.…”
Section: Estimation Methodologymentioning
confidence: 99%
“…Cole and Gunther (1996), Thomson (1992), Whalen (1991), Wilson (1995, 2000), and many others have modeled the failure of mature financial institutions, but only a handful of studies have modeled the failure of new financial institutions. 2 Hunter, Verbrugge, and Whidbee (1996) estimated a split-population duration model for de novo savings and loans; they found that credit risk, adverse economic conditions, low capital stocks, and cost inefficiencies all contributed to de novo thrift failure, and they also found evidence consistent with regulatory forbearance at failing thrifts. Santarelli (2000) estimated a proportional hazard model for de novo financial institutions in Italy and found that small start-ups and nonbank start-ups had higher risks of early exit than did large start-ups and bank start-ups.…”
Section: Recent Research On De Novo Banksmentioning
confidence: 99%
“…In states that had multiple capital requirements, this paper uses the requirement that applied to the smallest municipality, which was usually for 3,000 people. 17 Hunter, Verbrugge, and Whidbee (1996) provide some empirical support that minimum capital requirements reduced the likelihood of failure for de novo Savings and Loans in the 1980s.…”
mentioning
confidence: 99%
“…Hu et al (2004) find that, among loans, the rate of nonperforming debt increased in Taiwan during the 1990s. Hunter et al (1996) find that, for the United States in the 1980s, the percentages of nonperforming loans in a portfolio is associated with the portfolio owner's failure probability.…”
Section: Introductionmentioning
confidence: 97%